Individual corticosterone response to intermittent swim stress predicts a shift in economic demand for ethanol from pre-stress to post-stress in male rats - Robison, Christopher L.; Madore, Victoria; Cova, Nicole; Drugan, Robert C.; Charntikov, Sergios (Frontiers in Behavioral Neuroscience, 2024)
This study investigated the relationship between stress exposure and subsequent ethanol use, focusing on individual differences among male rats. We combined operant selfadministration with behavioral economics to assess how intermittent swim stress affects ethanol consumption. This approach allowed for a nuanced analysis of the transition from regular ethanol intake to stress-induced escalation in economic demand. Results showed a consistent rise in ethanol demand post-stress among subjects, irrespective of exposure to actual swim stress or a sham procedure. This increase may result from a two-week abstinence or an inherent rise in demand over time. Significantly, we identified a direct link between post-stress corticosterone levels and the demand for ethanol, considering baseline levels. This correlation was particularly pronounced when examining the shifts in both corticosterone levels and demand for ethanol post-stress. However, neither poststress corticosterone levels nor their change over time correlated significantly with changes in ethanol demand following a forced swim test that was administered 24 hours after the intermittent swim stress test. This suggests potential context-specific or stressorspecific effects. Importantly, pre-stress ethanol demand did not significantly predict the corticosterone response to stress, indicating that high ethanol-demand rats do not inherently exhibit heightened stress sensitivity. Our research brings to light the complex interplay between stress and ethanol consumption, highlighting the critical role of individual differences in this relationship. This research introduces a nuanced perspective, underscoring the need for future studies in the realm of stress and substance use to give greater consideration to individual variability.Note. This data is derived from individual economic demand values, utilizing the most suitable shared kappa parameter (k=10) to achieve the optimal model fit. EV = Essential Value; SD = Standard Deviation; SEM = Standard Error of the Mean.